The Adolescent Brain Cognitive Development (ABCD) study: Imaging acquisition across 21 sites. (August 2018) - Casey, B.J.; Cannonier, Tariq; Conley, May I.; Cohen, Alexandra O.; Barch, Deanna M.; Heitzeg, Mary M.; Soules, Mary E.; Teslovich, Theresa; Dellarco, Danielle V.; Garavan, Hugh; Orr, Catherine A.; Wager, Tor D.; et al.
Abstract: The ABCD study is recruiting and following the brain development and health of over 10, 000 9–10 year olds through adolescence. The imaging component of the study was developed by the ABCD Data Analysis and Informatics Center (DAIC) and the ABCD Imaging Acquisition Workgroup. Imaging methods and assessments were selected, optimized and harmonized across all 21 sites to measure brain structure and function relevant to adolescent development and addiction. This article provides an overview of the imaging procedures of the ABCD study, the basis for their selection and preliminary quality assurance and results that provide evidence for the feasibility and age-appropriateness of procedures and generalizability of findings to the existent literature.